The Effect of Income Tax Rates on the Financial Performance of Small and Medium Enterprises in Luzira, Nakawa Division - Kenneth Geofrey Higenyi (Uganda Christian University, 2023)
The general purpose of the study was to evaluate the effect of income tax rates on the financial performance of small and medium enterprises in Luzira and the specific objectives were; to assess the financial performance levels of small and medium enterprises in Luzira suburb, Nakawa division, to explore the effects of income tax rates on small and medium enterprises in Luzira suburb, Nakawa division and to determine the relationship between income tax rates and financial performance of small and medium enterprises. The researcher used purposive and systematic random sampling to get a representative sample size to obtain responses on the case study. On the effect of income tax rates on the financial performance of small and medium enterprises most of the respondents were unsatisfied with the income tax rates based on the sales turn over and some of the income tax rates administrators did not fully have information about income tax rates and its payers. The findings of the study showed that the introduction of income tax rates have adversely affected the net profit margin of small and medium enterprises and according to the responses, they strongly agreed that income tax rates affects the returns of their business. The researcher made the following recommendations as a way of reducing the burden of income tax rates on start-ups and small businesses as well as to increase the revenue or Luzira. Uganda Revenue Authority should simplify the tax codes and streamline compliance procedures, Uganda Revenue Authority should reduce income tax rates for SMEs, Uganda Revenue Authority should improve awareness amongst the, Uganda Revenue Authority should introduce target income tax incentives.
This is a dissertation.